2014
DOI: 10.3171/2013.8.jns13931
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery pulsatility index and cognitive improvement after carotid endarterectomy for symptomatic stenosis

Abstract: Object Transcranial Doppler (TCD) is frequently used to evaluate peripheral cerebral resistance and cerebral blood flow (CBF) in the middle cerebral artery prior to and during carotid endarterectomy (CEA). Patients with symptomatic carotid artery stenosis may have reduced peripheral cerebral resistance to compensate for inadequate CBF. The authors aim to determine whether symptomatic patients with reduced peripheral cerebral resistance prior to CEA demonstrate increased CBF and cognitive improvement as early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…As it has been proposed, cerebral autoregulatory mechanism contributes to the maintenance of sufficient mean flow velocity and decrease in the peripheral resistance in cerebral arteries to perfuse the ipsilateral hemisphere after the development of stroke. 20 The TCD ultrasound examination is a tool for determining the mean flow velocity and PI of cerebral arteries. An increased mean flow velocity of cerebral artery measured by TCD examination could be interpreted as an indirect indicative of increasing cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been proposed, cerebral autoregulatory mechanism contributes to the maintenance of sufficient mean flow velocity and decrease in the peripheral resistance in cerebral arteries to perfuse the ipsilateral hemisphere after the development of stroke. 20 The TCD ultrasound examination is a tool for determining the mean flow velocity and PI of cerebral arteries. An increased mean flow velocity of cerebral artery measured by TCD examination could be interpreted as an indirect indicative of increasing cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The PI was defined as the difference between peak systolic and end-diastolic velocities divided by the mean flow velocity of the same artery. 20 The NIHSS and TCD examinations were repeated on days 30, 60, and 90 during the follow-up period. All patients whose NIHSS scores were 0–1 or had a reduction in their NIHSS score more than 6 scores compared to their baseline NIHSS values were considered as responders.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral autoregulatory mechanisms will in these situations often reduce peripheral cerebral resistance. 49 In a population-based sample of middle-aged adults, ultrasound-derived indices of carotid atherosclerosis and MCA PI were associated, even after adjustment for established cardiovascular risk factors. However, the overall explained variance of MCA PI was low, suggesting other factors than atherosclerosis and cardiovascular risk factors to play an important role for MCA PI.…”
Section: Discussionmentioning
confidence: 94%
“…Lastly, it is important to emphasize that the results of our study are mainly applicable to subjects without carotid stenosis or eventual tandem lesions. Cerebral autoregulatory mechanisms will in these situations often reduce peripheral cerebral resistance …”
Section: Discussionmentioning
confidence: 99%
“…Further subgroup analysis indicated that cerebrolysin showed a superiority in patients with severe AIS. The cerebral autoregulatory mechanism made the spontaneous recovery of patients with AIS possible, especially in those with mild ischemic stroke 28. A high rate of spontaneous recovery under placebo might reduce the superiority of the cerebrolysin treatment arm.…”
Section: Discussionmentioning
confidence: 99%